Javanese Under Palm Oil Midrib of South Sumatera: Case Study of Aek Tarum Company (1989-2020) - Alif Bahtiar Pamulaan; Bondan Kanumoyoso (Criksetra: Jurnal Pendidikan Sejarah, 2022)
The New Order government that saw oil palm as an important commodity for Indonesia's economic development, initiating oil palm plantation development projects through the “Agro-industry” program in the 1980s. Intending to create jobs, the company is actually faced with the problem of procuring labor in plantations. This study was made as an effort to describe how companies overcome the difficulty of finding skilled workers in oil palm plantations in South Sumatra, with a case study of oil palm plantations of PT Aek Tarum which was established in 1989 in Mesuji District, Ogan Regency, Komering Ilir Regency. By using the historical method, this research was conducted through the stages of heuristics, source criticism, interpretation, and historiography. This research was conducted using an economic and socio-cultural approach. The results show that to overcome the problem of labor shortages in oil palm plantations, companies rely heavily on workers imported from outside the region. This dependence eventually gave birth to communities in oil palm plantations in South Sumatra, who were identified as Javanese.